AUTHENTICITY OR PROMOTIONAL CONTENT? THE INFLUENCE OF USER-GENERATED CONTENT AND CONTENT WRITING ON CUSTOMER ENGAGEMENT IN MALANG COFFEE SHOP - Reni Rupianti; Hardian Dwi Utomo; Nur’ Adilla; Firda Meisaroh (Branding: Jurnal Manajemen dan Bisnis, 2026)
This study aims to examine the influence of User-Generated Content (UGC) and Content Writing on Customer Engagement in coffee shops in Malang City. As the coffee industry in Malang continues to grow rapidly, businesses are increasingly utilizing social media to build relationships with consumers. This research employed a quantitative approach using a survey method involving 186 respondents selected through purposive sampling. Data analysis was conducted using Multiple Linear Regression. The results indicate that both UGC and content writing have a positive and significant influence on customer engagement. Furthermore, the findings reveal that UGC has a stronger influence than content writing in driving customer engagement. The study suggests that coffee shop owners should prioritize organic content from users to strengthen their brand presence. This research provides a practical model for coffee shop owners in Malang to optimize their digital marketing strategies by leveraging business dashboard analysis to monitor engagement metrics.